The abundance and sett ecological characteristics of the Asian badger (Meles leucurus) in the Northeast Tiger and Leopard National Park (NE China) - Jiawei Li; Dongrui Li; Yanwen Fu; Yiwen Ma; Jianping Ge; Limin Feng (Global Ecology and Conservation)
The sett is a crucial resource for badgers, serving various functions and significantly influencing their spatial ecology. The selection of sett sites is also a complex behavior. While there have been extensive ecological studies on the European badger (Meles meles), little is known about the Asian badger (Meles leucurus), particularly in China, making it difficult to evaluate their current survival status and establish conservation strategies. Therefore, we conducted a pioneering ecological study on the Asian badger, focusing on local population density and habitat selection within the Northeast Tiger and Leopard National Park, NE China. First, we surveyed badger setts in the study area and set camera traps to capture videos of badgers and estimate the number of individuals. The estimated badger density based on the main sett distribution (1.40 sett /km2) and group size (average of 3.01 ± 1.82 individuals per sett) was 4.21 ± 2.55 badgers /km2. Second, we set up random points in the study area and measured 12 habitat factors of 67 random point quadrats and 67 badger sett quadrats to establish which factors affect the habitat selection of badgers. Statistical tests, random forest algorithm, and generalized linear model were used to explain the sett selection criteria of Asian badgers. Statistical tests indicated a highly significant difference in slope (p < 0.01) and a significant difference in tree distance and aspect (p < 0.05) between sett quadrats and random point quadrats. After correction for multiple testing according to Holm, we found that differences in tree distance and aspect lost their statistical significance. However, the random forest algorithm and generalized linear model showed that the selection of sett location was influenced by tree distance, slope, and aspect. We conclude that badgers exhibit a preference for setts located near trees, steep slopes, and orientations facing north and northwest (316–45°). This is the first assessment of the abundance and sett selection of the Asian badger at the local population scale from Chinese nature reserves, providing new insights into the population ecology and habitat selection of the Asian badger in China, and assisting in the development of relevant conservation strategies and management.